Belydenis: Objektiewe waarheid of eksistensiele uitdrukking van geloof? - Steenkamp, L. J. S. (Hervormde teologiese studies, 1997)
Confession: Objective truth or existential expression of belief! Confession of belief originates when someone (the believer or the church) is so touched existentially by the Person, Jesus Christ, that he or she cannot help declaring that Jesus is the living Lord. This confession, therefore, becomes a lifestyle which has to be relived again and again. For this reason we never testify to our own insights or rational ideas about God, but to this meeting with God in Jesus Christ. Thus, it becomes clear that confession is different to religious lyrics or the knowledge of abstract truths which are only communicated rationally; it imlies a decision which carries a risk, but at the same time it Simply has to be repeated again and again in an existential" way by the believer.